Journal of Women's History Guide to Periodical Literature - Fischer, Gayle (Indiana University Press, 1992)
The political activism of the 1970s was followed by an explosion of feminist scholarship in the 1908s. The Journal of Women's History was founded to provide a means of disseminating that scholarship and to serve as the journal of record for the new area of women's history. As part of its mission, the journal began a compilation of periodical literature dealing with women's history. This first volume is drawn from more than 750 journals and includes material published from 1980 through 1990. There are forty subject categories, divided into numerous subcategories. The guide lists more than 5,500 articles; all are extensively cross-listed. In her foreword, Christie Farnham outlines the evolution of a journal devoted to women's history as a part of the transformation of the history profession by the feminist movement. Joan Hoff's introduction is a substantive discussion of the development of women's history as a discipline.